Comparison study on membrane fouling by various sludge fractions with long solid retention time in membrane bioreactor - Sun, Darren Delai (2015)
A membrane bioreactor (MBR) with sludge retention time (SRT) of 300 days was maintained for over 2 years. Polypropylene microfiltration (MF) membrane with pore size of 0.2 was used in the MBR system. The fouling behaviors of various sludge fractions from the MBR were studied and sub-divided resistances were analyzed. It was observed that was a dominant resistance during the filtration of activated sludge, contributing 63.0% and 59.6% to the total resistance for MBR and sequential batch reactor (SBR) respectively. On the other hand, played the significant role during the filtration of supernatant and solutes, varying between 54.54% and 67.18%. Compared with and , was negligible, and values remained constant at . Furthermore, resistances of all sludge fractions increased linearly with rising mixed liquor suspended solids (MLSS) concentration and growing trans-membrane pressure (TMP), while the relationship was inversed between fraction resistances and cross flow velocity (CFV). Among all fractions of activated sludge, suspended solid was the main contributor to the total resistance. A compact cake layer was clearly observed according to the field emission scanning electro microscopy (FE-SEM) images.